2022
DOI: 10.3390/met12030465
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Tribological Evaluation of Brake Disc Refurbishing Using Fe-Based Coating via Directed Energy Deposition

Abstract: In this paper, the refurbishing of worn-out brake discs by coating with powder via direct energy deposition (DED) is evaluated. A medium carbon steel powder was used to coat cast-iron discs. Deposition of this steel was carried out directly on the disc surface or, alternatively, after a previous deposition of a buffer layer made of stainless steel. It was seen that the use of a buffer layer ensured a good coating adhesion, despite the formation of cast microstructures at the interfaces between the disc and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For the PoD test, 14,400 m of the total sliding distance, a 2 m/s sliding speed, and 0.6 MPa of applied pressure were used. The selected PoD test conditions were intended to approximately simulate the mild wear condition, which is typical for braking systems [1,9,13]. The PoD test was also carried out on a GCI disc under identical testing conditions in order to provide a better reference point and an understanding of the coating properties comparatively.…”
Section: Wear Testmentioning
confidence: 99%
See 1 more Smart Citation
“…For the PoD test, 14,400 m of the total sliding distance, a 2 m/s sliding speed, and 0.6 MPa of applied pressure were used. The selected PoD test conditions were intended to approximately simulate the mild wear condition, which is typical for braking systems [1,9,13]. The PoD test was also carried out on a GCI disc under identical testing conditions in order to provide a better reference point and an understanding of the coating properties comparatively.…”
Section: Wear Testmentioning
confidence: 99%
“…For instance, carbon-ceramic composites have been established as an alternative to traditional brake disc materials since they display reduced wear rates and PM emission levels [6][7][8], However, because of the sophisticated production methods and unique features, these kinds of discs usually come with a higher price and are used for specific luxury cars. The application of coatings and disc surface treatments has also been investigated to reduce the wear and PM emissions of brake discs [2,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, carbonceramic composites have been established as an alternative to traditional brake disc materials since they display reduced wear rates and PM emission [7][8][9], However, because of the sophisticated production methods and unique features, these kinds of discs usually come with a higher price and for specific luxury cars. The application of coatings and disc surface treatments has also been investigated to reduce wear and PM emissions of brake discs [2,[10][11][12][13][14].…”
Section: Microstructure and Wear Resistance Of Fe3al Coating On Gci P...mentioning
confidence: 99%
“…In this regard, laser metal melting deposition and high-velocity oxygen fuel coating (HVOF) are emerging techniques to prepare coatings. [14][15][16][17][18] Recent academic studies have already shown the possibility of increasing friction coefficient and wear resistance using HVOF coating. Priyadarshini Jayashree 19 investigated the dry sliding friction and wear behavior of Cu-Sn composite and SiC-graphite against WC-Co-Cr-coated disks.…”
Section: Introductionmentioning
confidence: 99%
“…Since the braking behavior occurs on the surface, coating the brake disk surface is an option to improve mechanical and braking performance, as well as reduce cost and reuse exhausted brake disks. In this regard, laser metal melting deposition and high‐ velocity oxygen fuel coating (HVOF) are emerging techniques to prepare coatings 14‐18 . Recent academic studies have already shown the possibility of increasing friction coefficient and wear resistance using HVOF coating.…”
Section: Introductionmentioning
confidence: 99%